Student-Centric Learning as Educational Management Reform: Evidence of Social Retention Change in Adult Secondary Education - Bartoš, Pavel; Bočková, Kateřina; Pagáčová, Katarína; Stacho, Martin (Journal of Cultural Analysis and Social Change, 2026)
Student-Centric Learning (SCL) has become a central paradigm in contemporary educational reform, yet its empirical impact on adult learners in upper-secondary education remains insufficiently examined. This study investigates the effectiveness of SCL in reducing dropout rates and enhancing study completion within the context of adult upper-secondary education. Using a comparative design, two independent cohorts were analysed: a traditional distance study model (n = 6,723) and a student-centric model (n = 1,310). Completion rates differed dramatically between the two groups: 67.28% of learners graduated in the distance model, compared to 94.66% in the SCL cohort, a difference of 27.38 percentage points. Statistical testing confirmed the robustness of this effect (z = 20.135; p < 0.001), with learners in the SCL model being 1.41 times more likely to complete their studies and exhibiting 8.62 times higher odds of completion. The findings reveal that SCL functions as a synergistic constellation of pedagogical, relational, and organisational mechanisms including adaptive pacing, personalisation, continuous formative feedback, and high teacher–learner interaction, creating an environment that significantly strengthens learner persistence. Interpreted through a cultural-sociological lens, SCL emerges not only as a pedagogical approach but as an institutional and cultural intervention that enhances recognition, agency, and belonging, particularly for adult learners navigating complex life circumstances and historically higher rates of educational discontinuity. The study offers important implications for educational policy and institutional practice, demonstrating that learner-centred models can substantially reduce dropout, increase retention, and align with European strategies promoting inclusion, resilience, and lifelong learning. While limitations arise from the use of aggregated datasets and contextual differences between cohorts, the results provide strong quantitative evidence of the transformative potential of SCL in upper-secondary adult education. The study contributes to current debates on educational equity and institutional culture, showing that SCL constitutes a highly effective pathway towards more inclusive, adaptive, and socially responsive educational systems.